Broadband saturated absorption properties of bismuthene nanosheets. Issue 55 (29th October 2021) - Sun, Yan; Yuan, Junjie; Xin, Yi; Liu, Guowei; Zhang, Fang; Xing, Fei; Fu, Shenggui
Abstract : Bismuthene nanosheets were exfoliated by the LPE method. And the SA properties have been studies by open aperture Z-scan method. The results showed bismuthene nanosheets display broadband saturated properties in near-infrared wavelengths. Abstract : The nonlinear absorption properties of two-dimensional bismuthene nanosheets have great value for application in the photonics field. In this work, bismuthene nanosheets with a thickness of around 4 nm were prepared using the liquid phase exfoliation (LPE) method. The infrared waveband nonlinear absorption properties of bismuthene nanosheets were investigated using the open aperture Z-scan technique with four wavelengths of 950, 1064, 1200, and 1500 nm, respectively. Bismuthene nanosheets exhibited broadband saturated absorption (SA) properties at the infrared band. The lower saturated intensity indicated the advantages of bismuthene as a saturated absorber in the application of ultra-fast lasers in the infrared band.